1974
DOI: 10.1159/000271335
|View full text |Cite
|
Sign up to set email alerts
|

Moral Development Research

Abstract: From the moral development scale scoring manual, Kohlberg’s published works, and the research of his collaborators and others, an analysis was made of the evidence supporting the hierarchy of moral reasoning (from the lowest stage of blind acceptance of powerful authority to the application of abstract principles of justice and equality) and the claims put forth for the cross-cultural universality of the cognitive-developmental theory. Findings suggest that the definitions of stages and the assumptions underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…For example, Saxe (1982) demonstrated that the introduction of trade stores in a society prompted greater abstraction in the numeration system for related behaviors. Some have even argued that Kohlberg's higher stages simply reflect the abstract language of higher education in Western societies (e.g., terms such as justice, equality, reciprocity) and that use of the higher stage reasoning is a direct result of exposure to that abstract language (Simpson, 1974).…”
Section: Historical-ideological Biasmentioning
confidence: 99%
“…For example, Saxe (1982) demonstrated that the introduction of trade stores in a society prompted greater abstraction in the numeration system for related behaviors. Some have even argued that Kohlberg's higher stages simply reflect the abstract language of higher education in Western societies (e.g., terms such as justice, equality, reciprocity) and that use of the higher stage reasoning is a direct result of exposure to that abstract language (Simpson, 1974).…”
Section: Historical-ideological Biasmentioning
confidence: 99%
“…Kohlberg defends his system against the longstanding allegation of cultural elitism and ideological bias (e.g., Baumrind, 1978;Reid, 1984;Sampson, 1981;Schweder, 1982;Simpson, 1974;Sullivan, 1977) by attempting to distinguish between the intrinsic worth of persons and the value placed on their actions or judgments. Kohlberg defends his system against the longstanding allegation of cultural elitism and ideological bias (e.g., Baumrind, 1978;Reid, 1984;Sampson, 1981;Schweder, 1982;Simpson, 1974;Sullivan, 1977) by attempting to distinguish between the intrinsic worth of persons and the value placed on their actions or judgments.…”
Section: Sexual/cultural Difference Versus Deficitmentioning
confidence: 99%
“…... Justice "operations" of reciprocity and equality in interaction parallel logical operations or relations of equality and reciprocity in the non-moral cognitive domain. Indeed, as Emler (1983) suggests, Kohlberg's higher stages may constitute secular humanist values couched in the abstract language of individual rights, reciprocity, distributive justice, and equity (Simpson, 1974). But Kohlberg's preference for reasoning about the logical priority of a principle such as life over an alternative principle such as property rights represents the peculiar bias of Western industrialized society (Reid, 1984;Sampson, 1981), particularly, of its male members.…”
Section: Sexual/cultural Difference Versus Deficitmentioning
confidence: 99%
“…questions the existence of stages 5 and 6 altogether,Power (1994) suggests that stage 6 may not be a psychological stage but a philosophical position (as did Kohlberg's later work), whileHabermas (1979) argues for the addition of a seventh stage Simpson (1974),Sullivan (1977),. andSnell (1996) argue that Kohlberg's theory is based on Western ideology and is culturally biased, with higher moral development levels observed for Western cultures.…”
mentioning
confidence: 99%